Gene transfer into human lymphocytes by a defective human immunodeficiency virus type 1 vector. - Poznansky, M (1991)
Human immunodeficiency virus type 1 (HIV-1) proviruses containing deletions between nucleotides 301 and 319 express viral proteins but exhibit marked attenuation in the packaging of viral RNA into virions (A. Lever, H. Gottlinger, W. Haseltine, and J. Sodroski, J. Virol. 63:4085-4087, 1989; A. Aldovini and R. A. Young, J. Virol. 64:1920-1926, 1990). Here we report that such packaging-defective proviruses can provide trans-acting viral elements required for the transfer of a HIV-1 vector to Jurkat human lymphocytes. The transferred vector was unable to encode HIV-1 genes, indicating that the long terminal repeats and the immediate flanking viral sequences are sufficient for packaging, reverse transcription, and integration. The generation of replication-competent viruses in this system was reduced to undetectable levels by providing the trans-acting viral functions on two separate expression plasmids. This defective retroviral vector provides a means of efficiently introducing desired genetic elements, in the absence of HIV-1 genes, into HIV-1 target cells.